FRI0515 HSP90AA1, A CHAPERONE-MEDIATED AUTOPHAGY, IS A BIOMARKER ASSOCIATED WITH DEFECTIVE AUTOPHAGY IN OSTEOARTHRITIS. (June 2019) - Lorenzo, Irene; Pinto Tasende, Jose Antonio; Oreiro, Natividad; Blanco, Francisco J.; Carames, Beatriz
Abstract : Background: In osteoarthritis (OA), defects in cellular homeostasis, such as autophagy, are evident and precede joint damage (1). We have shown that there is a defect in autophagy in OA human chondrocytes and cartilage (2). Indeed, pharmacological activation of autophagy protects against joint damage (3). Our working hypothesis is that joint damage in OA could be due to a failure of autophagy that can be detected in the blood and tissue of patients. Objectives: The objective of this study is to identify biomarkers associated with autophagy defects that could facilitate the development of personalized therapeutic strategies to prevent OA progression. Methods: A comparative analysis of 35 autophagy genes was performed in blood from a Prospective OA Cohort of A Coruña (PROCOAC) of Non-OA and knee OA patients. Non-OA patients (Age: 61, 44 ± 1, 16 years; BMI: 25, 25 ± 0, 52; Females, n=18) and Knee OA patients (Age: 65, 50 ± 1, 05 years; BMI: 29, 55 ± 0, 67; Females, n=18, OA grade III-IV) were profiled using PrimePCR autophagy human panel array (Bio-Rad). Confirmatory studies of the candidate genes were performed in blood from Non-OA patients (Age: 60, 13 ± 1, 12 years; BMI: 24, 85 ± 0, 59; Females; n=30) and Knee-OA patients (Age: 68, 4 ± 1, 11 years; BMI: 29, 65 ± 0, 55; Females; n=30, OA grade III-IV) by Taqman Technology. A quantitative proteomic analysis of defective autophagy genes regulated upon deletion of Atg5 in human OA chondrocytes was performed by iTRAQ analysis. Moreover, the candidate gene was evaluated as a potential biomarker in human cartilage from Normal (n=19) and Knee-OA (n=20) patients and in both spontaneous aging (6, 12, 18, and 30 months old, n=3) and surgically-induced OA (10 weeks after surgery, n=4) in mice by immunohistochemistry. Remarkably, the consequences of candidate gene silencing on autophagy, FOXO signaling, inflammation, senescence and cell death by apoptosis was investigated by gene expression and flow cytometry. Results: 15 autophagy-related genes were downregulated in blood from knee OA patients compared to non-OA patients (p<0.05). Importantly, key autophagy-related genes, including ATG16L2, ATG12, ATG4B and MAP1LC3B, involved in relevant process including initiating autophagy, phagophore extension and autophagosome formation, were significant downregulated in knee OA patients (p<0.05). Interestingly, HSP90AA1 and HSPA8, chaperone-mediated autophagy genes involved in stress response and protein folding, were significant downregulated (p<0.001). In addition, several regulators of autophagy and apoptosis, such as BNIP3, BCL-2 and BCL2L1 were downregulated (p<0.01). Confirmatory studies for MAP1LC3B and HSP90AA1, showed a significant downregulation (p<0.001) in blood from knee OA patients. Remarkably, total proteome screening of human OA chondrocytes with defective autophagy, showed a significant reduction of HSP90AA1 (p<0.05). Remarkably, HSP90AA1 expression was reduced in OA cartilage (p < 0.01) and in spontaneous aging and surgically-induced OA in mice (p < 0.05). Interestingly, HSP90AA1 silencing increased LC3 and FOXO1 expression (p > 0.01), might be as a protective response, and increased NFκB and p16 expression (p < 0.05) at 48 hours. In addition, genetic deletion of HSP90AA1 increased cell death by apoptosis (p < 0.05). These data indicate that HSP90 might be a potential biomarker associated with defective autophagy in OA. Conclusion: We identified biomarkers of defective autophagy as a mechanism of central homeostasis, which gives us a general vision of the disease mechanisms linked to OA clinical reality. References: [1] Lotz MK, Caramés B. Nat Rev Rheumatol. 2011;7:579-87 [2] Caramés B, et al. Arthritis Rheum. 2010;62:791-801. [3] Caramés B, et al. Ann Rheum Dis. 2012;71:575-81. Disclosure of Interests: Irene Lorenzo: None declared, Jose Antonio Pinto Tasende: None declared, Natividad Oreiro: None declared, Francisco J. Blanco Consultant for: AbbVie, Bioiberica, BMS, GSK, Grünenthal, Janssen, Lilly, Pfizer, Regeneron, Roche, Sanofi, TRB Chemedica, and UCB, Beatriz Carames: None declared